Improving well-being and enhancing awareness in patients undergoing hemodialysis through the person-centered IARA model: an exploratory study - Di Marco, Sara; Padovan, Anna M.; Conti, Novella; Aimasso, Francesca; Viazzi, Francesca; Fontana, Vincenzo; Campanella, Dalila; Kuvačić, Goran; De Giorgio, Andrea (Frontiers in Medicine, 2024)
Chronic kidney disease (CKD) globally represents a significant health challenge, particularly among patients undergoing chronic hemodialysis. A careful nutritional and pharmacological prescription plays a key role in the effective management of these patients to optimize serum electrolytes, such as potassium, phosphorus, and protein intake. Furthermore, these patients can suffer psychological distress due to dietary restrictions and tight medication schedules. The present study explores the effectiveness of the person-centered IARA model in improving physiological markers and quality of life in CKD patients undergoing hemodialysis treatment. To demonstrate the effectiveness of the IARA model, 60 patients (M=40; F=20; 60.5 ± 9.9 years) undergoing thrice-weekly hemodialysis sessions were enrolled and randomly and blindly assigned to the Control or IARA group. The reduction in abnormal blood potassium, phosphorus, and total protein levels was investigated, alongside the psychological state through the SF-12 questionnaire. Preliminary findings showed a discernible reduction in the frequency of abnormal blood K (> 5.0 mmol/L) and P (> 4.5 mmol/L) levels in the IARA group compared to the Control group. In particular, such reductions were approximately 40% for K (OR = 0.57; 95% CL = 0.23/1.46) and about 15% for P (OR = 0.86; 95% CL = 0.27/2.74). A similar tendency was also observed for patient fluid intake during each hemodialysis session, with the frequency of higher-risk patients in the IARA group being 50% lower (OR = 0.50; 95% CL = 0.07/3.79) than that of the Control group. Although preliminary findings from this study suggest that the IARA model may have a positive effect on CKD patients' subjective well-being and quality of life (QoL), further research is needed to understand the long-term impact of the IARA intervention.